2020
DOI: 10.1007/s00167-019-05843-2
|View full text |Cite
|
Sign up to set email alerts
|

Slightly better pain relief but more frequently motor blockade with combined nerve block analgesia compared to continuous intraarticular analgesia after total knee arthroplasty

Abstract: Purpose Pain management after total knee arthroplasty (TKA) is still under debate. Continuous peripheral nerve blocks (PNB) can provide long pain relief but impair muscle function. Continuous intraarticular analgesia could result in longer pain relief than local infiltration analgesia without negative effects on muscle function. This study investigated the efficacy of pain control between PNB's and continuous intraarticular analgesia after TKA. Methods A prospective randomized study on 140 patients undergoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…[11] A recently conducted study compared the continuous intraarticular administration of ropivacaine with the combined continuous femoral, sciatic, and single-shot obturator nerve block. [12] A slightly better pain relief, but more frequent motor blockade, and even persisting quadriceps weakness were observed in the perineural catheter group.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…[11] A recently conducted study compared the continuous intraarticular administration of ropivacaine with the combined continuous femoral, sciatic, and single-shot obturator nerve block. [12] A slightly better pain relief, but more frequent motor blockade, and even persisting quadriceps weakness were observed in the perineural catheter group.…”
Section: Discussionmentioning
confidence: 81%
“…A couple of studies employed local anesthetic administered to only femoral nerve, [3][4][5][6][7][8][9][10] only in two studies provided blockade each of the three the nerves supplied the joint of the knee. [11,12] A systematic review reported less overall pain scores, opioid consumption, and more extended overall range on motion in the first 72 h after TKA, when femoral nerve block was combined with sciatic or obturator nerve block or with both. [18] In one of these studies, the femoral and sciatic nerve were blocked with or without obturator nerve blockade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is why recent studies emphasize continuous PNB, especially ACB [72] because continuous FNB impaired mobilization capability due to the weakness of the quadricep muscle. [73][74][75].…”
Section: Continuous Peripheral Nerve Blockmentioning
confidence: 99%
“…In addition, Runge et al (28) randomized 82 patients combined with triangular femoral block to reduce morphine use over LIA after TKA (6 vs. 20; p < 0,001). Finally, Lützner et al(29) found that a…”
mentioning
confidence: 99%